IZA Journal of Labor Policy - Rodríguez-Planas, Núria; Jimeno, Juan F.; Neumark, David
The IZA Journal of Labor Policy publishes scientific articles that are relevant for policy-making. This refers to papers addressing the impact of institutional settings and policy interventions on labor market outcomes, both from a theoretical as well as from an empirical point of view. In addition, the IZA Journal of Labor Policy publishes literature reviews and meta-analyses that synthesize existing research on policy relevant issues. What makes the IZA Journal of Labor Policy distinct from the vast majority of existing journals in economics is its focus on policy relevance rather than scientific innovation. We even welcome empirical replications as long as they constructively build upon existing findings. We expect papers that carefully address the causal identification of effects, but we do not regard statistical significance of empirical findings as a criterion for paper selection. Subject areas include evaluation of labor market programs and educational or other interventions that affect labor market outcomes, analysis of the relationship between institutions and labor market outcomes, and all public policy aspects of labor, education, welfare and related social policies, and retirement, including effective policy implementation. The IZA Journal of Labor Policy is central to IZA’s mission of supporting informed and research-based labor policy debates around the world. We want to make a serious contribution to a scientifically grounded understanding of what works when and how.